Effect of structural properties of unsaturated soils on the performance of biomineralized cementation - Zhuojun Feng; Xiaoli Li; Xuntao Liu; Bingkun Ma (Scientific Reports)
Abstract Enhancing the structural stability of Pisha sandstone soil is an important measure to manage local soil erosion. However, Pisha sandstone soil is a challenging research hotspot because of its poor permeability, strong soil filtration effect, and inability to be effectively permeated by treatment solutions. In this study, by adjusting the soil water content to improve the spatial structure of the soil body and by conducting unconfined compressive strength and calcium ion conversion rate tests, we investigated the effect of spatial distribution differences in microbial-induced calcium carbonate deposition on the mechanical properties of Pisha sandstone-improved soil in terms of the amounts of clay dissolved and calcium carbonate produced. The results demonstrate that improving the soil particle structure promotes the uniform distribution of calcium carbonate crystals in the sand. After microbial-induced carbonate precipitation (MICP) treatment, the bacteria adsorbed onto the surface of the Pisha sandstone particles and formed dense calcium carbonate crystals at the contact points of the particles, which effectively enhanced the structural stability of the sand particles, thereby improving the mechanical properties of the microbial-cured soils. The failure mode of the specimen evolved from bottom shear failure to overall tensile failure. In addition, the release of structural water molecules in the clay minerals promoted the surface diffusion of calcium ions and accelerated the nucleation and crystal growth of the mineralization products. In general, the rational use of soil structural properties and the synergistic mineralization of MICP and clay minerals provide a new method for erosion control in Pisha sandstone areas.